Strategi Peningkatan Sistem Penjaminan Mutu pada Lembaga Pendidikan Tinggi Islam - Arif, Miftakhul (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to analyze the strategy of the quality assurance system of Islamic higher education in improving the quality of institutions in the era of globalization and the industrial revolution 4.0. Quality assurance is seen as important as a quality control instrument in maintaining and developing the quality of education. This research uses a qualitative method with the type of library research. Data were obtained from scientific articles published in academic journals, research reports, and other related documents using documentation techniques. Data analysis was conducted through content analysis to evaluate the content of the collected literature. The results showed that the application of total quality management in education can encourage more effective and sustainable institutional change. In the context of higher education, assessment and accreditation that have been focusing on inputs and outputs can be improved through the application of total quality management that integrates inputs, processes, and outputs as a whole.